Sarcopenia in young adults with congenital heart disease - Zahra Khajali; Maryam Aliramezany; Fateme Jorfi; Homa Ghaderian; Majid Maleki; Hadi Malek; Sara Lotfian; Yasaman Khalili; Nasim Naderi (Wiley, 2022)
Abstract Background The chronic nature of congenital heart diseases (CHDs) leads to the activation of inflammatory and neurohormonal processes in the body, and there is a possibility of the occurrence of other complications such as sarcopenia. The aim of the present study was to evaluate sarcopenia prevalence in adult patients with CHDs. Methods Between April 2017 and December 2019, the current investigation recruited 85 patients from those referring to the Outpatient Adult CHD Clinic. Dual‐energy X‐ray absorptiometry (DXA) was employed to determine body composition and muscle mass. Handgrip strength is usually used to measure muscle strength. The 6‐min walk test (6MWT) and the 4‐m gait speed (4MGS) test were used for the evaluation of muscle performance. The presence of sarcopenia was defined based on the European Working Group on Sarcopenia in Older People. Results The study patients (44.7% male) were aged between 16 and 48 years. More than half of them (48 [56.5%] patients) were classified as severe complex CHDs. Most of the patients (73%) were asymptomatic. The diagnostic criteria of sarcopenia were fulfilled by 24 (28.2%) patients, whereas 15 patients fulfilled two criteria and nine patients met all three criteria for sarcopenia. According to the diagnostic criteria, 32.9% of patients had only a decreased skeletal muscle and considered as pre‐sarcopenia. Sarcopenia was more frequent in female patients (P = 0.02), patients with severe complex CHDs (P = 0.03), those with arterial desaturation (P = 0.001), ones with Eisenmenger syndrome (P = 0.002) and those without a history of corrective interventions (P = 0.03). The 6MWT measure was significantly reduced in the patients with sarcopenia (P < 0.0001). The patients with sarcopenia had also higher haemoglobin and haematocrit levels (P < 0.0001). Logistic regression multivariate analysis showed that the body mass index, haematocrit and 6MWT distance could be independently associated with sarcopenia in our study population. Conclusions The present study showed that adult patients with complex CHDs have impaired muscle strength and reduced muscle mass with a high prevalence of sarcopenia in spite of their young age.